The Effect of Auditor Competence and Auditor Independence on Audit Quality with Professional Skepticism as a Moderating Variable - Mochamad Andrianto Saputra (Cita konsultindo, 2026)
This study aims to analyze the effect of auditor competence and auditor independence on audit quality, with professional skepticism as a moderating variable. The phenomenon of audit failures indicates that there are still problems in the quality of audits produced by auditors. This study employs a quantitative approach using a survey method by distributing questionnaires to 365 auditors working at public accounting firms in the DKI Jakarta and Tangerang areas. Data analysis was conducted using Moderated Regression Analysis with the assistance of SPSS version 26. The results show that auditor competence has a positive and significant effect on audit quality with a beta coefficient of 0.486, and auditor independence has a positive and significant effect on audit quality with a beta coefficient of 0.392. Professional skepticism is proven to moderate the relationship between auditor competence and audit quality with an interaction coefficient of 0.156, and to moderate the relationship between auditor independence and audit quality with an interaction coefficient of 0.142. The R-square value increases from 0.621 to 0.712 due to the moderating effect. This study implies that public accounting firms need to develop comprehensive strategies to enhance competence, maintain independence, and foster auditors’ professional skepticism in order to achieve optimal audit quality.